Characterization of large-scale genomic differences in the first complete human genome - Xiangyu Yang; Xuankai Wang; Yawen Zou; Shilong Zhang; Manying Xia; Lianting Fu; Mitchell R. Vollger; Nae-Chyun Chen; Dylan J. Taylor; William T. Harvey; Glennis A. Logsdon; Dan Meng; et al. (Genome Biology, 2023)
Abstract Background The first telomere-to-telomere (T2T) human genome assembly (T2T-CHM13) release is a milestone in human genomics. The T2T-CHM13 genome assembly extends our understanding of telomeres, centromeres, segmental duplication, and other complex regions. The current human genome reference (GRCh38) has been widely used in various human genomic studies. However, the large-scale genomic differences between these two important genome assemblies are not characterized in detail yet. Results Here, in addition to the previously reported “non-syntenic” regions, we find 67 additional large-scale discrepant regions and precisely categorize them into four structural types with a newly developed website tool called SynPlotter. The discrepant regions (~ 21.6 Mbp) excluding telomeric and centromeric regions are highly structurally polymorphic in humans, where the deletions or duplications are likely associated with various human diseases, such as immune and neurodevelopmental disorders. The analyses of a newly identified discrepant region—the KLRC gene cluster—show that the depletion of KLRC2 by a single-deletion event is associated with natural killer cell differentiation in ~ 20% of humans. Meanwhile, the rapid amino acid replacements observed within KLRC3 are probably a result of natural selection in primate evolution. Conclusion Our study provides a foundation for understanding the large-scale structural genomic differences between the two crucial human reference genomes, and is thereby important for future human genomics studies.